STUDI INTERAKSI DAN PREDIKSI TOKSISITAS SENYAWA TURUNAN ASAM AMINO, ASAM ORGANIK, FLAVONOID, GLIKOSIDA, KUMARIN, TURUNAN POLISAKARIDA, DAN VIT E SEBAGAI ANTI-AGING TERHADAP PROTEIN MATRIKS METALLOPROTEINASE-1, CARBONIC ANHYDRASE-1, DAN TYROSINASE RELATED PROTEIN-1 SECARA IN SILICO - Khoerunnisa Kosim, Ridha
Indonesia is a region with a high ultraviolet radiation intensity from sunlight. Excessive intensity of sun exposure can cause skin-aging caused by free radical formed. Naturally, human skin has protection function against ultraviolet rays by producing melanin, which can causes pigmentation in excess concentration. Because of the limited anti-aging compounds used in skincare and their side effects, it is necessary to develop a novel anti-aging compound with better efficacy and safety. This research aimed to discover anti-aging candidates by predicting the interaction of the compounds against key targets using molecular docking simulation and their toxicity using in silico method. The targets used were matrix metalloproteinase-1 fibroblast collagenase-1 (PDB ID: 966C), carbonic anhydrase-1 (PDB ID: 6F3B) and tyrosinase-related protein-1 which play important role in skin-aging. The three-dimensional structures of the compounds were drawn using Avogadro and optimized with ORCA 4.2.1 program using Density Functional Theory (DFT), default spin, B3LYP with 6-31G(d) method. Docking parameters were validated, and the simulation was performed using the AutoDock 4.2.3 program. The docking results were analyzed using Biovia Discovery Studio 21.1.0 and the toxicity of the compounds was predicted using Toxtree 3.1.0.1851 and Vega 1.1.5. Compounds with the best interaction prediction were apigenin, brazilein, and quercetin because it has the most negative binding free energy and similar interaction with the native ligand against protein. Apigenin, brazilein, and quercetin toxicity were predicted high based on Cramer rules, while both apigenin and quercetin were predicted safe based on Kroes-TTC. Brazilein was predicted negligible low toxicity on the latter method. Based on Toxtree result, apigenin was predicted to have the risk for skin sensitization, while brazilein and quercetin were predicted to give a risk of mutagenic and caused skin sensitization. Toxicity prediction using Vega gave results that apigenin, brazilein, and quercetin were possible to cause acute and chronic toxicity in moderate level.